Job satisfaction among employees in Giant Hypermarket Plentong Johor Bahru / Hud Paiman - Paiman, Hud (Faculty of Business and Management, 2010)
Job satisfaction is very subjective words which it can come from many causes. Thus, in understanding and knows how satisfy each person in some company, this research are must gone through in order to answer of that from our head. There are a great many reasons for the popularity of the topic, including that organizations are faced with changes like never before. This is a study on one company that is Giant Hypermarket Plentong (GHPT). Giant Hypermarket Plentong is centre of Southern Region that consist 16 outlets including hypermarkets, superstore, Guardian and Cold Storage. Its problem is their employees have increasing turnover each year as well as absenteeism problems. This is study focus on the relationship between turnover, absenteeism and motivation and job satisfaction. This study also using sample size of 100 respondents and choose non-probability as sampling technique. Furthermore, this studies also using primary and secondary data. Findings are interpreted using frequency and percent, descriptive statistics, cross tabulation, regression and also correlation. Finally there are some conclusions and some recommendation for future research.